The Frequency-Independent Wideband Planar Log-Periodic Antenna For Multiband Applications (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
In this article, a frequency-independent wideband log–periodic (LP) multiband antenna is proposed and its measurement results in terms of different performance parameters are analyzed. This proposed antenna is designed and implemented to support transmission modes with multi resonances at 0.8, 1.8, 2.37 and 2.94 GHz. The FR-4 substrate material is used to design the suggested antenna which has a fixed dimension of 160 ×160 mm2.  They can operate at GSM 800, GSM 1800, Wi-Fi and LTE bands with wider bandwidth due to its design shape and coaxial feeding technique. This symmetrical pair of novel ring-turnstile 2 arms planar log-periodic (LP) multiband antenna has a peak realized gain of 3.4, 5.8, 5.2 and 5 dBi at different resonant frequencies and is suitable for a various communication system. In terms of the S-parameter (S11), voltage standing wave ratio (VSWR), peak realised gain, surface current distribution and radiation pattern, the proposed LP multiband antenna output parameters are analysed. Besides, it has promising values of return loss (RL) less than -10 dB, VSWR less than 4 at all resonant frequency, and gain more than 3.8 dBi. The proposed antenna is a promising candidate for various communication systems because of its suitable radiation pattern properties and rising peak gain..